Jan y Julia estan enfermos - Rettich, Margret; Westphal, Catharina; Terzi, Marinella (Barcelona : Edebe, 2016)
When Julia gets sick, she stays home from nursery school and goes to the doctor, while her brother Jan is told to stay away from her so he does not catch what she has.
Keywords: Sick -- Fiction; Twins -- Fiction; Siblings -- Fiction; Family life -- Fiction; Spanish language materials; Spanish language materials